國小師生全球暖化迷思概念與成因之探討 - 沈彥甫; Yen-Fu Shen (2019)
本研究的目的在探討國小高年級學生與國小教師「全球暖化」的迷思概念，研究對象為桃園縣、新北市與高雄市國小高年級學生520人與國小教師71人，以紙筆問卷調查收集研究對象之迷思概念，佐以事件晤談方式來深入探討研究對象迷思概念及其思考模式，以瞭解迷思概念的成因。 研究結果顯示國小高年級學生與國小教師對於全球暖化議題的知識的確存有迷思概念，例如：認為臭氧層破洞會造成全球暖化，北極海冰融化會造成海平面上升，溫室效應是環境問題需要被解決，中秋節烤肉會增加我國的總排碳量，我知道石化燃料指的就是煤、石油、天然氣，再生能源是環保且便宜的能源，不再成長的老樹仍持續具有減碳的功效，全球暖化會導致下酸雨，使用電動車不會產生碳排放，我們只要做好節能減碳就足以因應全球暖化等等。 而本研究之研究對象其迷思概念類型約可分為以下幾種：直覺判斷、知識不足、生活經驗誤用、教學誤導、邏輯謬誤、名詞錯誤等，最後歸納研究發現與結論，並提出改進方式與建議。 This study aims to investigate high-grade elementary school students and elementary school teachers 'global warming' misconceptions, the study of Taoyuan County, Taipei and Kaohsiung, the new elementary school students 520 people and 71 elementary school teachers to paper pen questionnaire study of misconceptions collection, combined with the way the event in depth interview study of misconceptions and thinking to understand the causes of misconceptions. The results showed high-grade elementary school students and elementary school teachers for the knowledge of global warming issues there really are misconceptions, such as: that the ozone hole will cause global warming, Arctic sea ice melt will cause sea level rise, greenhouse effect is environmental issues need to be resolved, Mid-Autumn Festival BBQ will increase our total carbon emissions, I know refers to fossil fuels coal, oil, natural gas, renewable energy is environmentally friendly and cheap energy, no longer has the continued growth of the trees cut carbon effect, acid rain, global warming will lead to the next, use of electric vehicles will not produce carbon emissions, reduce carbon emissions as long as we do enough in response to global warming and so on. The object of this research about the types of misconceptions can be divided into the following categories: intuitive judgments, lack of knowledge, life experience misuse, teaching misleading, logical fallacy, the term error, and finally summarized findings and conclusions, and propose ways to improve and recommendations. 環境教育研究所